Offset contracts: international contracts and brazilian legislation constraints in the bidding process - Menin Junior , Romeu Felix (Revista Coleta Científica, 2020)
The theme of this article is: Offset contracts: international contracts and the obstacles of Brazilian legislation in the bidding process. The following problem was investigated: Does the Brazilian State have an agenda to mitigate contractual barriers between the international actors involved in the Offset agreements? The following hypothesis was considered: Is there specific legislation designed to accompany the compensation clauses throughout the Offset project? The general objective is: To identify the historical background of the international legislative evolution up to the present. The specific objectives are: To enter the historical points of creation; how it was adapted to the national territory. This work is important for an operator of the Law, for society and science as a whole, because the lack of specific legislation designed to accompany the compensation clauses throughout the Offset project makes the international legislative equalization go beyond the policy budgetary authority conferred on the State. This is a qualitative theoretical research lasting five months. As a result of the research conducted, it is concluded that the Offset is an instrument of political and strategic influence that should not be contained in the military area, the Offset can assist technological and industrial progress as a whole, in the case of the dynamics of each contractual agreement. International practice, it is impracticable to develop a suitable legislative context for the reception of a rigid execution linked to the Offset agreement.